Olive stone as a renewable source of biopolyols - Matos, M.C. (2009)
The purpose of this work was to establish the feasibility of converting the olive stone residue by means of both total and partial oxypropylation. In the first case, the oxypropylation reaction conditions are chosen in order to promote extensive grafting, thus assuring a complete “liquefaction” of the material and, in the second case, partial oxypropylation would limit the reaction to the outer shell in view of the preparation of all-“olive stone” composites. This approach involves a straightforward transformation of the olive stone particles outer layer, giving rise to a thermoplastic matrix around its unreacted reinforcing inner structure, as already applied to cellulose and starch. To the best of our knowledge, oxypropylation was never applied to olive-stone.